Parameters Of Immunological And Molecular-Genetic Interrelation In Men With Impaired Fertility - Aripova T.U; Gaibullaev A.A; Yarmukhamedov A.S; Khozhdaeva N.Kh; Yuldashev M.A; Fayzullaeva N.Ya. (Procedia of Social Sciences and Humanities, 2022)
To date, it has been established that the causes of male infertility are very diverse. Among the causes of male infertility are considered ejaculatory, sexual, anatomical changes in the structure of the genital organs, endocrine disorders, inflammatory processes, immunological factors, various disorders of spermatogenesis, environmental factors, and much more. In the structure of the causes of infertile marriage, male infertility occupies up to 40%, and it should be given the same close attention as female infertility. It is known that genetic factors cause at least 30-50% of all cases of severe forms of infertility in men. Spermatogenesis is a complex biological process that depends on a precisely controlled cascade of activation and deactivation of certain genes. The result of the work of these genes is the process of maturation of spermatozoa from progenitor cells (spermatogonia). In humans, more than 2000 genes are involved in this process. Due to genetic disorders, various forms of infertility in their etiology and severity can occur: from minor violations of spermatogenesis to complete dysfunction of the gonads. Among the gene factors associated with azoospermia, mutations/variants of the CFTR gene are the most common. They can cause cystic fibrosis (CF) and CBAVD syndrome (congenital bilateral aplasia of vas deferens), resulting in bilateral aplasia and obstruction of the vas deferens. The study of the features of immunological reactivity in male infertility has not only a pronounced theoretical, but also practical interest. Of particular note is the lack of information about the state of the cytokine profile and its relationship with the parameters of immunity in infertility in men, as well as the impact of these disorders on the processes of spermatogenesis.